Improving performance of fully scalable, flexible transparent conductive films made from carbon nanotubes and ethylene-vinyl acetate - Sturdza, BK; Lauritzen, AE; Zhou, S; Bennett, AJ; Form, J; Christoforo, MG; Dalgliesh, RM; Snaith, HJ; Riede, MK; Nicholas, RJ (Elsevier, 2022)
We report process improvements for the fabrication of single-walled carbon nanotube ethylene-vinyl acetate transparent conductive films. CNT:EVA films demonstrate high resilience against folding and can replace the external dopant in a spiro-OMeTAD based hole selective contact of n-i-p perovskite solar cells achieving a steady-state efficiency of 16.3%. The adapted process is fully scalable, and compared to previous reports (Mazzotta et al., 2018) lowers the material cost dramatically and improves DC to optical conductivity ratio by two orders of magnitude to σdc/σop = 3.6 for pristine and σdc/σop = 15 for chemically doped films. We analyse the microstructure of our films via small angle neutron scattering and find a positive correlation between the long range packing density of the CNT:EVA films and the σdc/σop performance. Increasing monomer ratio and chain length of the EVA polymer improves resilience against bending strain, whereas no significant effect on the CNT wrapping and electrical conductivity of resulting films is found.